Olah Rasa Timur Jawa: Strategi Preservasi Warisan Budaya Lintas Generasi - Indiarti, Wiwin; Nurchayati, Nunuk (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
This article is based on the Community Partnership Program (PKM) which seeks to solve the problems faced by Osing indigenous community, especially the Archipelago Indigenous Youth Front (BPAN) of Osing from the aspects of preservation strategies and revitalization of ritual meals. The solutions offered from this program are the making of ritual meals cooking book, digital documentation (pictures, writings, sounds and videos) stored in the form of Digital Video Disc (DVD) and ritual meals cooking training for young people. The activities are in the form of making a book containing ritual meals recipes and way of cooking, training module which contains the way to cook ritual meals and ritual meals training for young people while the mentoring method was carried out by the team continuously during the period of the PKM program. The outputs are training module, a book with recipes and way of cooking of ritual meals, digital documentation, and ritual meals training model for young people.